2020
DOI: 10.1200/go.22.00005
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Opportunities of Oncofertility Practice in Nine Developing Countries and the Emerging Oncofertility Professional Engagement Network

Abstract: PURPOSE Oncofertility practice continues to grow in developing countries despite the lack of health care services, especially those related to cancer care. The purpose of this study is to further explore oncofertility practice in these countries and identify opportunities for field-wide coalescence. METHODS We generated a survey to learn more about oncofertility practice in nine developing countries within our Oncofertility Consortium Global Partners Network—Mexico, Colombia, Guatemala, Argentina, Chile, Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The underutilization of sperm cryopreservation by male patients with cancer is secondary to various potential barriers, including lack of provider and patient awareness regarding available fertility preservation options; delay in diagnosis with insufficient time for referral to reproductive specialists before treatment; and financial burden on patients along with other logistical, cultural, religious, and ethical impediments. 20,21 Studies have demonstrated that oncologists offer semen cryopreservation to less than 25% of their adolescent patients. 22 Acute illness has been cited as a barrier for up to 40% of male patients who do not receive counseling.…”
Section: Barriers To Fertility Preservationmentioning
confidence: 99%
“…The underutilization of sperm cryopreservation by male patients with cancer is secondary to various potential barriers, including lack of provider and patient awareness regarding available fertility preservation options; delay in diagnosis with insufficient time for referral to reproductive specialists before treatment; and financial burden on patients along with other logistical, cultural, religious, and ethical impediments. 20,21 Studies have demonstrated that oncologists offer semen cryopreservation to less than 25% of their adolescent patients. 22 Acute illness has been cited as a barrier for up to 40% of male patients who do not receive counseling.…”
Section: Barriers To Fertility Preservationmentioning
confidence: 99%
“…20 Considering that treating breast cancer in LMICs poses additional challenges including inequities in access to screening and effective therapeutic options, 21-23 it is of paramount importance to investigate potential disparities in survivorship care, particularly in the field of oncofertility, also considering the different reproductive behaviors and fertility-related challenges compared with Western countries. 24,25 Notably, lack of clear evidence exists on how survivorship care in young women with breast cancer is managed in LMICs. 26…”
Section: Introductionmentioning
confidence: 99%
“…20 Considering that treating breast cancer in LMICs poses additional challenges including inequities in access to screening and effective therapeutic options, [21][22][23] it is of paramount importance to investigate potential disparities in survivorship care, particularly in the field of oncofertility, also considering the different reproductive behaviors and fertility-related challenges compared with Western countries. 24,25 Notably, lack of clear evidence exists on how survivorship care in young women with breast cancer is managed in LMICs. 26 The present survey aimed at investigating knowledge, practice, and attitudes of physicians involved in cancer care and practicing in LMICs on fertility and pregnancyrelated issues in young (≤ 40 years) women with breast cancer to portray treatment patterns and to raise awareness on the needs related to these important aspects of the care of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although surveys have been used to assess oncofertility practice barriers in oncology and reproductive medicine professionals, they lack complete and valid development. For example, Salama et al (2018) surveyed the barriers to oncofertility in one of six categories without providing information on the survey development process and validation. In addition, Wang et al (2019) used an online survey to assess healthcare professionals' oncofertility attitudes and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to individual patient factors, other barriers to oncofertility care exist. A survey from nine developing countries found that barriers to oncofertility practice include lack of awareness among healthcare providers, cultural and religious constraints, lack of insurance coverage and funding to help support oncofertility programs, and high out-of-pocket costs for patients (Salama et al, 2018). Moreover, evidence from China shows significant gaps in oncofertility knowledge among reproductive healthcare professionals (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%